The Influence of Work Autonomy, Workload, Work Bornage and Interpersonal Conflict on Nurse Performance in Patient - Abdul Haris; L Sulaiman; Saimi Saimi (poltekkes kemenkes mataram, 2021)
The problem of work stress is still a trend in various parts of the world. In Europe, the problem of work stress ranks second after musculoskeletal disorders. Sources of work stress which consist of autonomy, workload, work saturation and interpersonal conflicts are a challenge for hospitals in terms of employee performance issues. The purpose of this study was to determine the effect of work autonomy, workload, work saturation and interpersonal conflict on the performance of nurses in the Inpatient Installation of RSUD Bima.The research design used was non-experimental quantitative analytical observational. The research sample was 154 nurses in the inpatient room. The analysis in this study used univariate, bivariate and multivariate analysis with multiple linear regression with 95% confidence level or nilai <0.05.The results showed that the value of work autonomy (0.000), workload (0.013), work boredom (0.014) and interpersonal conflict (0.006) < 0.05 which means that all variables affect the performance of nurses and result of logistic regresion it was found that the most dominant variable was interpersonal conflict with the highest Odds Ratio value of 3.764,which means that interpersonal conflict was the most influential variable on the performance of nurses.Based on the results of the study, it can be concluded that work autonomy, workload, work saturation and interpersonal conflict affect the performance of nurses, and the most influential variable is work saturation with the largest t value of 2.486. It is recommended for the Head of Nursing and Head of Room to evaluate the performance of nurses in the room to the maximum, and make a performance-based supervision program and assessment of service users